PENGARUH VIDEO ANIMASI TENTANG BAHAYA MEROKOK TERHADAP PENGETAHUAN DAN SIKAP REMAJA (Jurnal Kesehatan Siliwangi, 2021)
Smoking causes impaired lung growth and development in children and adolescents which can lead to chronic health problems as they grow older. The increasing prevalence of smoking in adolescents is influenced because they are easily influenced by the environment. Some of the motivations behind smoking are to get acknowledgment (anticipatory beliefs) to eliminate disappointment (reliefing beliefs) and assume that their actions do not violate norms (permission beliefs/positive). This research is motivated by the increasing incidence of smoking in Indonesia. The incidence of smoking in the working area of ​​the Jayamekar Health Center UPT is quite high, 39.80%, according to data from the Jaya Mekar Health Center in 2020. The highest smoking incidence is in adolescents 15-18 years with a percentage of 57.8% male and 6.4% female smokers. This study aims to analyze the effect of animated video media on knowledge and attitudes regarding the dangers of smoking in adolescents at SMAN 2 Padalarang, West Bandung Regency in 2021. This study uses a quantitative design, with a One-Group Pretest-Posttest Design to measure the effect of animated video media on the dangers of smoking. smoking on the knowledge and attitudes of adolescents at SMAN 2 Padalarang. The data in this study were the results of the Pretest Posttest questionnaire distributed to the respondents. The subjects of this study were 97 students of class XI at SMAN 2 Padalarang who smoked. Knowledge and attitude data were processed using the Wilcoxon Signed Test. The results of this study indicate that knowledge and attitudes through animated video education increased from the category of good scores on knowledge, only 92 people (94.9%) to 96 people (98.97%), while attitudes were only 19 people (19.58%). to 25 people (25.8%). Based on the analysis test conducted, there was a significant value for knowledge of 0.018 and attitude of 0.002, which means <0.05, then the hypothesis was accepted. So it can be concluded that there is a significant effect of providing education through animated videos on increasing the knowledge and attitudes of XI grade boys at SMAN 2 Padalarang, West Bandung Regency.